Nurse’s knowledge and perceptions on communicative hypnosis: an observational study - Carvello, Maicol; Lupo, Roberto; Muro, Milena; Grilli, Gloria; Rubbi, Ivan; Artioli, Giovanna (Acta Biomedica Atenei Parmensis, 2021)
Background Much evidence shows that hypnotic communication can have a pain-relieving effect and reduce complications such as anxiety, insomnia and depression. Whenever this technique was applied, the use of pharmaceuticals was reduced, there were less side effects, shorter hospitalization timesframes and lower treatment costs.Aim of the study Evaluate the knowledge and perceptions of nurses about hypnotic communication and the causes for which this technique is not frequently used. A secondary objective pointed to measuring the effectiveness of an educational event on hypnosis.Method The evaluation was done by administering an anonymous and voluntary survey, in a pre-test and post-test modality to nurses subscribed to a formative event on hypnotic communication organized by the Nursing Order, Province of Ravenna.Results 78 nurses participated in the study. The analysis of the pre-test results show a gap of knowledge regarding hypnotic communication. The main causes were found regarding the lack of use for hypnotic communication: stereotypes and prejudices related to this technique and insufficient university education.Conclusions The implementation of this technique, effective and efficient under various aspects, requires a preliminary creation of culture regarding this theme, capable of surpassing the stereotypes and resistances brought by a lack of theoretical elements.